Advertising / A Decision-Making Approach - Frazer F. Charles; Patti H. Charles (The Dryden Press, 1988)
Background for Understanding Advertising, Marketing and Adverising Environments: Campaign Foundations, Advertising Decision Making: Pre-Campaign Issues, Advertising Decision Making: Campaign and Development and Execution, Advertising Decision Making: Message Delivery, Contemporary Issues in Advertising, Appendixes.
Background for Understanding Advertising, Marketing and Adverising Environments: Campaign Foundations, Advertising Decision Making: Pre-Campaign Issues, Advertising Decision Making: Campaign and Development and Execution, Advertising Decision Making: Message Delivery, Contemporary Issues in Advertising, Appendixes.